2023
DOI: 10.1021/jacsau.3c00132
|View full text |Cite
|
Sign up to set email alerts
|

Minimalist Design for Solar Energy Conversion: Revamping the π-Grid of an Organic Framework into Open-Shell Superabsorbers

Abstract: We apply a versatile reaction to a versatile solid: the former involves the electron-deficient alkene tetracyanoethylene (TCNE) as the guest reactant; the latter consists of stacked 2D honeycomb covalent networks based on the electron-rich βketoenamine hinges that also activate the conjugated, connecting alkyne units. The TCNE/alkyne reaction is a [2 + 2] cycloaddition−retroelectrocyclization (CA-RE) that forms strong push− pull units directly into the backbone of the framework�i.e., using only the minimalist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Both COFs possessed sufficient driving force for the 2e – ORR toward H 2 O 2 production based on thermodynamic consideration. As shown in the photoluminescence (PL) spectrum (Figure S15a), while DHAA-Tp COF exhibited fluorescence intensities, TCNAQ-Tp COF showed nonemissive under the light excitation at 400 nm, which was probably caused by nonradiative transition . We further investigated the behavior of excitons by time-resolved fluorescence decay.…”
Section: Resultsmentioning
confidence: 96%
“…Both COFs possessed sufficient driving force for the 2e – ORR toward H 2 O 2 production based on thermodynamic consideration. As shown in the photoluminescence (PL) spectrum (Figure S15a), while DHAA-Tp COF exhibited fluorescence intensities, TCNAQ-Tp COF showed nonemissive under the light excitation at 400 nm, which was probably caused by nonradiative transition . We further investigated the behavior of excitons by time-resolved fluorescence decay.…”
Section: Resultsmentioning
confidence: 96%
“…[ 24 ] Very recently, He et al reported facile modification of the main skeleton of alkynes on COF to give a framework holding persistent radicals for high PCE together with solar‐vapor conversion efficiencies > 96%. [ 25 ] However, there are few studies on the application of D–A structured motifs prepared from CA–RE reactions for photothermal conversion while most of the studies focus on non‐linear optics and photoluminescent materials. [ 26 ] Even though the aforementioned COFs bearing D–A junctions have been adopted for photothermal conversion, these COFs are not nanoscale or insoluble to be utilized for PTT.…”
Section: Introductionmentioning
confidence: 99%